ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN SISTEM TABELA DI DESA TAMADUE KECAMATAN LORE TIMUR KABUPATEN POSO - Wahiduddin, Wahiduddin; Effendy, Effendy; Sulaeman, Sulaeman (AGROTEKBIS, 2019)
The Village of Tamadue is one of the centerproductions in Paddy field at East Lore Sub-district. Rice is the main sourcefood of Indonesian?s population-mostly it is cultivated in wetland rice. Wetland Paddyfarming is one of the income sourcesand job opportunities for rural communities, therefore it needs proper management by using productionfactors efficiently. Nowadays, rice cultivation is required more efficient. The system that fulfill the criteria is the Direct Seeding System (Tabela).The purpose of this research is to observe the income of rice farming system using tabela system at Tamadue Village, East Lore Sub-district, Poso District.This research was conducted from November to December 2016 atTamadue Village, East Lore Sub-district, Poso District, the determination of research location was chosen purposively, the respondents determination using Slovin formula and obtained as 32 people. The analytical tool used in this research is Income Analysis.The result of analysis showed that the average income received by rice farmers using tabela system atTamadue Village, East lore District of Poso is Rp.34,016,353 / MT with the average land area owned by respondents is 2.4 ha. The average income is derived from the average revenue of Rp.48,850,000 minusthe average total cost of Rp.14,833,648.